Borboletas na rede : uma netnografia sobre práticas de bulimia e anorexia entre jovens mulheres no ciberespaço - Santos, Cristina Oliveira dos (2016)
The aim of this research is to explore the virtual community of the the butterflies' WhatsApp group that promotes interaction between females people between the ages of 10 to 35 years old. The members of said group are pro-eating disorders of the so called brazilian “pro-Anas” and “pro-Mias”, adept to practice anorexia and/or bulimia, respectively. The approach to this work is justified because members are more active in virtual communities, interacting more frequently and building social ties. I will use the virtual ethnography or netnography to discover the world views, identity construction and personal relations that are created by participants, as well as analysis of virtual social networks. As a result of this dissertation was concluded that pro-Ana is pro-Mia are aware of the negative effects of these disorders in their bodies and their lives, but believe that all the sacrifice to get achieve their desire to have a lean body are valid because away from the lipophobicity, a form of fat’s demonization. Moreover, the constant support of the participants in virtual communities proved to be something so strong as to create links between people who were once unknown and now assumed a big importance to the pro-Ana and pro-Mia that their lives revolve around the eating disorder and friendships established within the Butterflies group.